STRATEGI MANAJEMEN SUMBER DAYA MANUSIA STARBUCKS INDONESIA DALAM PENGELOLAAN PARTNER - Fadhil Maulana Tanjung; Susi Delmiati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
This study examines the human resource management (HRM) practices implemented by Starbucks Indonesia (PT Sari Coffee Indonesia) in managing more than 5,400 partners across over 580 outlets in 59 cities. Employing a qualitative descriptive approach through document analysis and literature review, this study identifies seven core HRM pillars: (1) a partner-centric philosophy; (2) structured recruitment and selection; (3) a systematic 30-day Barista Basics training program using the Teaching Model; (4) a transparent career development path via the Learning-Owning-Advising (L-O-A) framework; (5) competitive total-rewards compensation; (6) a strong organizational culture anchored in five core values (Craft, Results, Courage, Belonging, Joy); and (7) continuous performance management through operational excellence tools. Findings suggest that Starbucks Indonesia's HRM success lies in its ability to integrate global best practices with local cultural sensitivity, treating people development as a strategic investment rather than a cost.Keywords: Human Resource Management, Starbucks Indonesia, Partner Development, Organizational Culture, Operational Excellence